Highly sensitive thermoelectric touch sensor based on p-type SnO x thin film - Vieira, Eliana Maria Fernandes (2019)
Here, the ability of using p-type tin oxide (SnOx) thin films as a thermal sensor has been investigated. Firstly, the thermoelectric performance was optimized by controlling the thickness of the SnOx film from 60 up to 160 nm. A high Seebeck coefficient of +263 mu V K-1 and electrical conductivity of 4.1 x 10(2) (S m(-)(1)) were achieved in a 60 nm thick SnOx film, due to a compact nanostructured film and the absence of the Sn metallic phase, which was observed for the thicker SnOx film leading to a typical thermoelectric transport properties of a n-type Sn film. Moreover, x-ray photoelectron spectroscopy revealed the co-existence of SnO (79.7%) and SnO2 (20.3%) phases in the 60 nm thick SnOx film, while the optical measurements revealed an indirect gap of 1.8 eV and a direct gap of 2.7 eV, respectively. The 60 nm-SnOx thin film have been tested as a thermoelectric touch sensor, achieving a V-signal/V-noise approximate to 20 with a rise time <1 s. Therefore, this work provides an efficient way for developing highly efficient thermal sensors with potential use in display technologies.